2020
DOI: 10.1098/rsos.200766
|View full text |Cite
|
Sign up to set email alerts
|

Three minutes to change preferences: perceptual fluency and response inhibition

Abstract: Perceptual fluency and response inhibition are well-established techniques to unobtrusively manipulate preference: objects are devalued following association with disfluency or inhibition. These approaches to preference change are extensively studied individually, but there is less research examining the impact of combining the two techniques in a single intervention. In short (3 min) game-like tasks, we examine the preference and memory effects of perceptual fluency and inhibition individually, and then the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…At the same time, however, research from Maille et al (2020) has shown that even something as simple as presenting graspable objects in the background (e.g., mugs, wine glasses, and yoghurt pots) can lead to an increase in the viewer's intention to purchase non-graspable target products Although Maille and colleagues' study concerned non-food products, the same principles might well be expected to apply in the case of edible food products. It is, though, best not to place anything (such as objects) between the viewer and the food (Cannon, Hayes, & Tipper, 2020;Makris, Hadar, & Yarrow, 2011;McKean, Flavell, Over, & Tipper, 2020), as this will likely interfere with the viewer's embodied mental simulation of eating the food thus, in turn, reducing their liking for what they see.…”
Section: Insert Figure 3 About Herementioning
confidence: 99%
“…At the same time, however, research from Maille et al (2020) has shown that even something as simple as presenting graspable objects in the background (e.g., mugs, wine glasses, and yoghurt pots) can lead to an increase in the viewer's intention to purchase non-graspable target products Although Maille and colleagues' study concerned non-food products, the same principles might well be expected to apply in the case of edible food products. It is, though, best not to place anything (such as objects) between the viewer and the food (Cannon, Hayes, & Tipper, 2020;Makris, Hadar, & Yarrow, 2011;McKean, Flavell, Over, & Tipper, 2020), as this will likely interfere with the viewer's embodied mental simulation of eating the food thus, in turn, reducing their liking for what they see.…”
Section: Insert Figure 3 About Herementioning
confidence: 99%
“…Ultimately, the ease (or fluency) versus difficulty of the bodily movements required to manipulate food from plate or bowl to mouth by means of different kinds of cutlery are very often culturally-determined and may either enhance, or impede, a diner's enjoyment of a particular food/multisensory eating experience (cf. McKean et al, 2020). As such, proprioceptive fluency (or disfluency) is another important factor that can enhance or negatively impact the experience of what we are eating.…”
Section: The Postural Aspects Of Eatingmentioning
confidence: 99%